Combination of Polydopamine Coating and Plasma Pretreatment to Improve Bond Ability Between PEEK and Primary Teeth - Teng, Rui; Meng, Yuchen; Zhao, Xiaodan; Liu, Jie; Ding, Rui; Cheng, Yilong; Zhang, Yunhe; Zhang, Yanfeng; Pei, Dandan; Li, Ang (Frontiers in Bioengineering and Biotechnology, 2021)
Preformed crowns are preferred to reduce the failure risk of restoration of primary teeth, but some drawback of conventional material is still a main barrier for their clinical use. Polyether etherketone (PEEK) with a tooth colored, high-performance thermoplastic polymer, has been recognized as a promising alternative to manufacture the restoration of primary teeth. However, the hydrophobic surface and low surface energy of PEEK make it hard to establish a strong and durable adhesion. In this study, we have evaluated a modification method of polydopamine (PDA) coating with plasma pretreatment for PEEK films by physical and chemical characterization, bonding properties and biocompatibility. The surface properties of PEEK were well characterized by scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS). The adhesive strength of the PEEK films was greatly improved without significant reduction of proliferation rate of human gingival fibroblasts cells in MTT and Live/Dead assays. Therefore, PDA coating with plasma pretreatment may give a new solution for effective clinical application of PEEK in primary performed crowns.